2011
DOI: 10.1681/asn.2010040403
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nanofibers Preconditioned with Stem Cell Secretome Are Renoprotective

Abstract: Stem cells may contribute to renal recovery following acute kidney injury, and this may occur through their secretion of cytokines, chemokines, and growth factors. Here, we developed an acellular, nanofiber-based preparation of self-assembled peptides to deliver the secretome of embryonic stem cells (ESCs). Using an integrated in vitro and in vivo approach, we found that nanofibers preconditioned with ESCs could reverse cell hyperpermeability and apoptosis in vitro and protect against lipopolysaccharideinduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 67 publications
(82 reference statements)
1
45
0
Order By: Relevance
“…Similar studies by our group and others have shown limited inflammatory responses with synergistic activity of passively loaded cytokines or growth factors. 1,3,4,17 As a vital next step, it was important to confirm the maintenance of activity of ionically sequestered drugs after loading into MDP carriers. Because suramin is known to have distinct effects on growth factors/growth factor receptors, we utilized suramin-releasing gels to determine biological activity.…”
Section: Preservation Of Biological Activity In Ionically Cross-linkementioning
confidence: 99%
“…Similar studies by our group and others have shown limited inflammatory responses with synergistic activity of passively loaded cytokines or growth factors. 1,3,4,17 As a vital next step, it was important to confirm the maintenance of activity of ionically sequestered drugs after loading into MDP carriers. Because suramin is known to have distinct effects on growth factors/growth factor receptors, we utilized suramin-releasing gels to determine biological activity.…”
Section: Preservation Of Biological Activity In Ionically Cross-linkementioning
confidence: 99%
“…4g). Gels were pre-loaded with the secretome from stem cells, which contains more than 36 secreted proteins, and subsequently used to study the effect on a lipopolysaccharide model of acute kidney injury in mice and an ischemia-reperfusion model of kidney injury in mice [95]. The preconditioned nanofibers protect the kidney against injury by delivery of the secretome of stem cells, which is proposed to be the cause of the improvement resulting from stem cell treatment of acute kidney injury.…”
Section: Biosynthetic Supramolecular Hydrogels Based On β-Sheetsmentioning
confidence: 99%
“…These preconditioned nanofibers in these experiments exerted cytoprotective effects by preventing LPS-induced apoptosis of tubular cells and podocytes through modulation of Rho kinase activation. One enticing feature of the study by Wang et al 13 is the in vivo confirmation of in vitro results. Preconditioned nanofibers prevented proteinuria, reduced renal function impairment, and exhibited antifibrotic and anti-inflammatory properties in mice with LPS-induced AKI.…”
mentioning
confidence: 91%
“…It is also unknown whether biodegradable nanofibers can also act as acellular delivery platforms for the secretome released from stem cells. In this issue of JASN, the article by Wang et al 13 offers unprecedented findings shedding light on these issues. Through an integrated in vitro and in vivo approach, they assessed the effect of self-assembling nanofibers preconditioned with secretome from mouse ESCs on the kidney after LPS-induced acute kidney injury (AKI).…”
mentioning
confidence: 99%
See 1 more Smart Citation